2013
DOI: 10.1089/neu.2012.2828
|View full text |Cite
|
Sign up to set email alerts
|

Epicritic Sensation in Cervical Spinal Cord Injury: Diagnostic Gains Beyond Testing Light Touch

Abstract: Applied as a bedside test of gross dorsal column function, the testing of light touch (LT) sensation is of high clinical value in the diagnosis of human spinal cord injury (SCI). However, the assessment of overall dorsal column deficit by testing only LT may be limited, because the dorsal column pathway conveys several large diameter afferent modalities (e.g., sensation of touch, two-point discrimination, and proprioception). Therefore, the objective of this study was to compare the epicritic sensation assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, SWM was significant and more sensitive to small gains between 1 and 3 months, something not found with LT (C6-C8). The present results suggest that SWM is sensitive to minor impairments, which are less detectable by LT testing; findings also confirmed in cross-sectional studies by Kalsi-Ryan et al 13 and Velstra et al 34 These authors observed greater sensitivity of the SWM in individuals with acute and chronic SCI compared with the values reported when using LT.…”
Section: Discussionsupporting
confidence: 89%
“…However, SWM was significant and more sensitive to small gains between 1 and 3 months, something not found with LT (C6-C8). The present results suggest that SWM is sensitive to minor impairments, which are less detectable by LT testing; findings also confirmed in cross-sectional studies by Kalsi-Ryan et al 13 and Velstra et al 34 These authors observed greater sensitivity of the SWM in individuals with acute and chronic SCI compared with the values reported when using LT.…”
Section: Discussionsupporting
confidence: 89%
“…Measurements were made by pressing each monofilament to the skin. Measurements started with the smallest diameter monofilament (an ascending method of threshold testing) [ 19 ]. The monofilament was held in contact with the skin until it bent, and then removed after 1 s. Participants were asked to close their eyes and to indicate whether they could sense the monofilament stimulation [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…AIS D patients could potentially be studied with interventions as well if the outcome measures used do not have ceiling effects for the AIS D subgroup. For studies including cervical AIS D patients, measures such as electrical perceptual thresholds, 21 and measures of manual dexterity 22 could be employed to avoid the challenges of a ceiling effect that are inherent in the more conventional measurement techniques used. The AIS CD group that converted was entirely made up of AIS C patients that converted to D. This group generally started at a lower point than the AIS D patients; showed significant recovery in the first 3 months and then followed a similar recovery profile as the AIS D group.…”
Section: Kalsi-ryan Et Al Upper Limb Recovery Profilesmentioning
confidence: 99%